Evaluation of Different Glycoforms of Honeybee Venom Major Allergen Phospholipase A2 (Api m 1) Produced in Insect Cells - Blank, Simon; Michel, Yvonne; Seismann, Henning; Plum, Melanie; Greunke, Kerstin; Grunwald, Thomas; Bredehorst, Reinhard; Ollert, Markus; Braren, Ingke; Spillner, Edzard (Protein and Peptide Letters, 2011)
Allergic reactions to hymenoptera stings are one of the major reasons for IgE-mediated anaphylaxis. However, proper diagnosis using venom extracts is severely affected by molecular cross-reactivity. In this study recombinant honeybee venom major allergen phospholipase A2 (Api m 1) was produced for the first time in insect cells. Using baculovirus infection of different insect cell lines allergen versions providing a varying degree of cross-reactive carbohydrate determinants as well as a non glycosylated variant could be obtained as secreted soluble proteins in high yields. The resulting molecules were analyzed for their glycosylation and proved to show advantageous properties regarding cross-reactivity in sIgE-based assays. Additionally, in contrast to the enzymatically active native protein the inactivated allergen did not induce IgE-independent effector cell activation. Thus, insect cell-derived recombinant Api m 1 with defined CCD phenotypes might provide further insights into hymenoptera venom IgE reactivities and contribute to an improved diagnosis of hymenoptera venom allergy.
Keywords: MUXF-HAS